De te fabula narratur. Writing and agency according to Writing and Reading Workshop in the upper secondary school - Stefania Leondini (Italiano a scuola)
This paper outlines the general principles of workshop-based teaching as applied to upper secondary school, linking theoretical reflection on writing to its practical and operational application, based on many years of teaching experience. The discussion focuses in particular on the production of the most common text types and on the concept of agency, drawn from the U.S. workshop model.